Generic POLCA : a production and materials flow control mechanism for quick response manufacturing - Fernandes, N.O.G. (2012)
A production and materials flow control mechanism for quick response manufacturing (QRM) is proposed. This is called generic paired-cell overlapping loops of cards with authorization (GPOLCA). It is an adaptation of the POLCA mechanism developed as part of the QRM strategy. GPOLCA implements an input–output control order release strategy based on an inventory of production authorization cards instead of materials. It is best suited for companies that manufacture large variety of products with variable demand. A description of GPOLCA is made together with a comparative study of its performance in relation with other mechanisms namely MRP and POLCA. The results show that GPOLCA attains better performance.